David Wolf : Smoked Out - Book 6 - Carson, Jeff ([Place of publication not identified] : Cross Atlantic Publishing, 2015)
"With over a dozen mending bones and other injuries wreaking havoc on his body, along with a shredded spirit twisting his sanity, former sheriff David Wolf is in no shape for any sort of action. But when FBI surveillance units move into the valley and surround his house, it seems he's about to have no choice. Wolf quickly learns, however, things are not what they seem, and a trap has been set with him as the prey. If he wants to live long enough to bring justice for the only woman he's ever loved and to see his son grow into a man, broken body or not, he must move, and move fast."--Back cover.
Keywords: Murder -- Fiction -- Investigation; Sheriffs -- Fiction; Sheriffs; Murder -- Investigation; Colorado -- Fiction; Colorado; Fiction; Detective and mystery fiction; Detective and mystery fiction